The relevance of vagueness for translation: examples from english to portuguese - Santos, Diana (TradTerm, 1998)
In the present paper, the concept of vagueness will be taken up in detail, in order to make it more precise and to pin down its relevance for translation. In addition to view (some) translation choices as contrastive vagueness, I will argue that grammar too has to be contrasted, introducing the concepts of grammatical vagueness and contrastive grammatical vagueness. The problems these phenomena pose for translation are illustrated in the realm of tense and aspect with real translation pairs from (American) English to (European) Portuguese.